Carbon taxation and inflation: Evidence from the European and Canadian experience - Maximilian Konradt; Beatrice Weder (Graduate Institute of International and Development Studies, 2021)
What is the effect of climate policies on inflation and economic activity? Answering this question is critical for central banks trying to achieve price stability. This paper studies the experience from existing carbon taxes in Canada and Europe, introduced over the last 30 years. Based on two separate empirical approaches, we find that carbon taxes do not have to be inflationary and may even have deflationary effects. In particular, our evidence suggests that the increase in energy prices was more than offset by a fall in the prices of services and other non-tradables. Our results are robust for Europe and Canada, as well as a number of different country groupings. At least in case of British Columbia, a contraction in household incomes and expenditures, in particular among the richer households, could explain the deflationary effect.
Keywords: E31; E50; Q54; Q43; 330; Carbon taxes; carbon pricing; inflation; monetary policy; climate change